2008
DOI: 10.1039/b808157c
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray pair distribution function analysis of a metakaolin-based, KAlSi2O6·5.5H2O inorganic polymer (geopolymer)

Abstract: The atomic structure of geopolymers is often described as amorphous with a local structure that is equivalent to that of crystalline zeolites. However, this structural relationship has never been quantified beyond a first-nearest-neighbor bonding environment. In this study, the short to medium range ($1 nm) structural order of metakaolin-based KAlSi 2 O 6 $5.5H 2 O geopolymer was quantified and compared to zeolitic tetragonal leucite (KAlSi 2 O 6 ) using the X-ray atomic pair distribution function technique. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 43 publications
11
87
0
2
Order By: Relevance
“…White et al 15 observed that once heated to 1000 • C, the structure of the geopolymer (K 2 O·Al 2 O 3 ·4SiO 2 ·11H 2 O) began to crystallize and form leucite, as analyzed by the neutron pair distribution function. Bell et al 11,16 reported that the major reflection for leucite first appeared from geopolymer (K 2 O·Al 2 O 3 ·4SiO 2 ·11H 2 O) upon 1050 • C by XRD and that long range order occurred at 1060 • C by X-ray atomic pair distribution function technique.…”
Section: Materials and Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…White et al 15 observed that once heated to 1000 • C, the structure of the geopolymer (K 2 O·Al 2 O 3 ·4SiO 2 ·11H 2 O) began to crystallize and form leucite, as analyzed by the neutron pair distribution function. Bell et al 11,16 reported that the major reflection for leucite first appeared from geopolymer (K 2 O·Al 2 O 3 ·4SiO 2 ·11H 2 O) upon 1050 • C by XRD and that long range order occurred at 1060 • C by X-ray atomic pair distribution function technique.…”
Section: Materials and Methodologiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] A significant feature is that on heating a geopolymer will be converted into a leucite ceramic. [8][9][10][11][12][13][14][15][16][17][18] Therefore, geopolymer technology provides a new route to fabricate advanced ceramics of advantageously low cost and near net-shape forming, an attractive feature in industrial applications. It was reported in literatures that van Deventer et al from the University of Melbourne and Kriven et al from the University of Illinois at UrbanaChampaign have systematically studied the effects of Si/Al ratios and alkali cations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disordered nature of the geopolymer binder phase is highly amenable to analysis by this technique, as has been discussed in recent reviews [1,17], and significant advances in the understanding of geopolymer nanostructure have been obtained by both X-ray [18,19] and neutron [20,21] pair distribution function analysis. In situ analysis of geopolymer formation has previously been undertaken by a variety of laboratory and beamline techniques, including in particular the use of in situ energy-dispersive X-ray diffractometry to provide direct kinetic information regarding gel structure formation using high-energy synchrotron radiation [22,23].…”
Section: In Situ Neutron Pair Distribution Function Analysis Of Geopomentioning
confidence: 99%
“…The PDF approach using SR has also been employed to study several other amorphous (or ill-crystalline) phases in cement research including ASR gel, [34] silica fume, [35] metakaolin [36,37] and geopolymers. [38][39][40] 3.2.2.…”
Section: Techniques For Characterizing Amorphous Phasesmentioning
confidence: 99%